The State of Evidence in Prostate Artery Embolization - Qamhawi, Zahi; Little, Mark W. (Seminars in Interventional Radiology, 2022)
Prostate artery embolization (PAE) has emerged over the past two decades as a minimally invasive, nonsurgical treatment for benign prostatic hypertrophy (BPH). While the majority of evidence for PAE stems from retrospective cohort studies, several seminal randomized controlled trials have been performed comparing short-term outcomes of PAE to transurethral resection of prostate (TURP) and against a sham procedure. Across clinical trials, PAE demonstrates consistent improvement in urological symptoms and quality of life in patients with BPH with low complication rates. When compared to TURP, the results are comparable, but there is a trend for better outcomes in certain clinical parameters with TURP. PAE is a suitable option for patients who are not surgical candidates, prefer nonsurgical treatment with an earlier return to routine activities, and wish to better preserve sexual function.
Keywords: prostate artery embolization; benign prostatic hypertrophy; lower urinary tract symptoms; transurethral resection prostate; prostate; embolization; interventional radiology